Effect of Some Operating Parameters on Quality of Corn Flakes Supported by Some Additives Document Type : Original Article - Entsar, S. Abdou; Marwa, M. Helmy; Entsar, N. Mohamed (Food Technology Research Journal, 2023)
The main objective of this work was to study the effect of some operating parameters on quality of corn flakes ‎supported by some additives. Extruded snacks were prepared using different blends (A, B and C) of grits corn, flakes defatted soy bean and flakes oats [A (50:30:20), B (40:35:25) and C (30:40:30)] respectively, with different moisture contents depend on wet basis (12, 17, 22, 27 and 32 %) and two extruder die diameters (0.6 and 1.0 cm). The chemical compositions of the three blends were determined. It was found that blend C had the higher protein, fibers, fat, moisture content and ash. The results showed that the changing of die diameter and moisture content affected the physical properties of extrudates (expansion ratio, bulk density, hardness, water absorption capacity, water activity, color) for all different blends (A, B and C). Sensory evaluation was subjected (odor, texture, taste, color and overall acceptability), the overall acceptability was 9 for blend (C) with moisture content 22%.